2008
DOI: 10.1161/circulationaha.107.733451
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Temporal Behavior of the Planar QRS-T Angle in Patients With Nonischemic Cardiomyopathy

Abstract: Background-The planar QRS-T angle can be easily obtained from standard 12-lead ECGs, but its predictive ability is not established. We sought to determine the predictive ability of the planar QRS-T angle in patients with nonischemic cardiomyopathy and to assess QRS-T angle behavior over time. Methods and Results-Baseline QRS-T angles from 455 patients in the Defibrillators in Nonischemic CardiomyopathyTreatment Evaluation (DEFINITE) trial were measured. All patients had nonischemic cardiomyopathy, New York Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 35 publications
(21 reference statements)
2
88
0
2
Order By: Relevance
“…A planar QRS-T angle > 90° has been shown to be a significant predictor of a composite end point of death, appropriate implantable cardioverter-defibrillator shock, or resuscitated cardiac arrest in non-paced, mild to moderately symptomatic patients with non-ischaemic cardiomyopathy. A widening QRS-T angle has been proposed to represent a continuum of worsening underlying pathology and outcome [23]. Discordant LBBB was more frequent in patients with EF < 50% in our study.…”
Section: Discussionsupporting
confidence: 48%
“…A planar QRS-T angle > 90° has been shown to be a significant predictor of a composite end point of death, appropriate implantable cardioverter-defibrillator shock, or resuscitated cardiac arrest in non-paced, mild to moderately symptomatic patients with non-ischaemic cardiomyopathy. A widening QRS-T angle has been proposed to represent a continuum of worsening underlying pathology and outcome [23]. Discordant LBBB was more frequent in patients with EF < 50% in our study.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies demonstrated that a spatial QRS-T angle wider than 100°is associated with the presence of cardiac disease and increased cardiovascular mortality. 20,21 Pavri et al 22 recently demonstrated that a planar QRS-T angle wider than 90°is associated with an increased incidence of appropriate device shocks and mortality. In the present study, these cutoffs (100°for the spatial and 90°for the planar QRS-T angle) were applied.…”
Section: Ecg Analysismentioning
confidence: 99%
“…29 In our population of ischemic primary prevention ICD recipients, patients with a wide planar QRS-T angle demonstrated a HR of 2.5 for the need of defibrillator backup and 3.1 for all-cause mortality. In the recently published post hoc analysis of the DEFINITE trial by Pavri et al, 22 the planar QRS-T angle was analyzed as a predictor of the composite end point of appropriate device therapy, mortality, and resuscitated cardiac arrest in a population with nonischemic cardiomyopathy. In this study, the HR of a planar QRS-T angle wider than 90°for the occurrence of appropriate device therapy was 1.95 (95% CI, 1.24 to 3.08).…”
Section: Risk Stratification With the Qrs-t Anglementioning
confidence: 99%
See 1 more Smart Citation
“…41 FQRSTA is a very powerful predictor of cardiovascular events (e.g., myocardial ischemia), 42 sudden cardiac death, [13][14][15][16][17]43 appropriate ICD therapy, 44,45 all-cause mortality, 15,[33][34][35][36][37] increased cardiac-related hospitalizations, 17,35 reduced left ventricular function, [34][35][36]46 especially in patients with postinfarction, [13][14][15][16][17] acute myocardial infarction with LVEF ࣘ40%, 47 the elderly, 12 chronic dialysis, [18][19][20] heart failure with preserved ejection fraction, 17 and ischemic stroke 48 considered stronger than any of the classical cardiovascular risk factors. 16,17 Risk factors leading to an elevation in FQRSTA were related to coronary artery disease, dialysis, poor-controlled hypertension, 49,50 pulmonary arterial hypertension, 51 left/right ventricular hypertrophy, 51-54 dilated left ventricle, 55 lower LVEF, 56 DM, 57, 58 smoking, [57][58][59] and female gender.…”
Section: Dm and Fqrstamentioning
confidence: 99%